Necessidades formativas no campo pedagógico: a perspectiva do desenvolvimento profissional de docentes iniciantes da UEFS - Moreira, Daniele de Jesus Gomes (2014)
The aim of the research was to examine the pedagogic necessities of beginner teachers of the State University of Feira de Santana (henceforth UEFS, from Universidade Estadual de Feira de Santana) in order to provide professional teaching development. The research question was: what necessities (in relation to pedagogic formation) do the beginner teachers from UEFS point out? A theoretical framework deals with the teaching education, pedagogic knowledge and practice, and also with the concepts of formative necessities and professional teaching development in higher education such as: Cunha (2004), Ribeiro (2012; 2010; 2004), Pimenta (2008; 2006), Grillo (2008), Masetto (2012) among others. The locus of the research was UEFS and the subjects were 49 teachers with the minimum of 5 years working as teachers in the university. The collection and production of data was made by a questionnaire with open and closed questions. For the analysis of the closed ones it was used a statistic program called SPSS 20. For open questions it was used the analysis of content (BARDIN, 2009). The analysis of the data collected from closed questions did not reveal any expressive necessities in regard to pedagogic practice, however, the data from open questions revealed different kinds of formative necessities such as: teaching planning, classroom management, learning assessment, students’ cognitive difficulties and new information and communication technologies. The results highlight the necessity of systematic institutional actions concerning to the pedagogic formation of teachers, and also keeping the autonomy, protagonist role of the teacher and the continuity of the formation. Therefore, it is recommended the construction of an institutional policy whose focus is the professional teaching development.